"I feel lonely, I don't understand you when you talk, and I find it hard to breathe". Analysis of the emotional tensions of physical education students in the Spanish setting of COVID-19. (April 2022) - Hortigüela-Alcala, David; Chiva-Bartoll, Oscar; Hernando-Garijo, Alejandra
Abstract: The aim of this research is to analyse the emotional tensions experienced by PE students in the setting of the COVID-19 pandemic. Twenty-four students participated in the study. A qualitative methodology was used in which, taking into account the safety and prevention conditions established for the COVID-19 situation, three categories of analysis were obtained: a) experiences regarding the use of the face mask; b) experiences regarding physical distancing; and c) social interaction between students. The researchers' logbooks and three discussion groups were used as data collection instruments. The results show how the COVID-19 safety measures generated emotional changes in students.